Soil Organic Carbon Storage under Biofuel Cropping Systems in a Humid, Continental Climate. (1st September 2018) - Ibrahim, Mostafa A.; Chua‐Ona, Teresita; Liebman, Matt; Thompson, Michael L.
Abstract : Core Ideas: Biofuel cropping systems did not lead to increases in soil C stocks after 7 yr. Only the continuous corn cropping system led to an increase in bulk density after 7 yr. The correlation between soil organic C and clay content weakened after 7 yr. The aim of this work was to investigate the impact of perennial and annual biofuel cropping systems on soil bulk density (BD) and soil organic carbon (SOC) concentration and stocks in a humid, continental climate. The model system chosen was in central Iowa. The cropping systems studied were: continuous corn ( Zea mays L.) (CC), continuous corn with a rye ( Secale cereale L.) cover crop (CCW), reconstructed prairie with no fertilizer amendments (Pr), and reconstructed prairie that received annual N fertilizer amendment (PrF). A large‐scale field experiment was established in 2008, and each treatment was replicated four times. Soil cores were collected from the replicate plots at depths of 0 to 15 cm and 15 to 30 cm after harvest in 2008 and 2015, and soil BD and SOC were determined. The prairie‐based cropping systems (Pr and PrF) maintained low soil BDs over the seven growing seasons. While mean BD in the corn‐based cropping systems (CC and CCW) increased over seven growing seasons from 1.41 Mg m −3 in 2008 to 1.49 Mg m −3 in 2015, SOC stocks in the four treatments were statistically unchanged ( p ≤ 0.05). We found that SOC concentration in the upper 15 cm of the soil was strongly correlated with clay content in 2008 ( R 2 = 0.89, p < 0.0001), but that the association between clay and SOC had weakened somewhat in the annual cropping systems after 7 yr of crop production ( R 2 = 0.52, P < 0.0015).